Requirement of DNA Repair Mechanisms for Survival of Burkholderia cepacia G4 upon Degradation of Trichloroethylene - Yeager, Chris M. (American Society for Microbiology, 2001)
A Tn5-based mutagenesis strategy was used to generate a collection of trichloroethylene (TCE)-sensitive (TCS) mutants in order to identify repair systems or protective mechanisms that shield Burkholderia cepacia G4 from the toxic effects associated with TCE oxidation. Single Tn5 insertion sites were mapped within open reading frames putatively encoding enzymes involved in DNA repair (UvrB, RuvB, RecA, and RecG) in 7 of the 11 TCS strains obtained (4 of the TCS strains had a single Tn5 insertion within a uvrB homolog). The data revealed that the uvrB-disrupted strains were exceptionally susceptible to killing by TCE oxidation, followed by the recA strain, while the ruvB and recG strains were just slightly more sensitive to TCE than the wild type. The uvrB and recA strains were also extremely sensitive to UV light and, to a lesser extent, to exposure to mitomycin C and H(2)O(2). The data from this study establishes that there is a link between DNA repair and the ability of B. cepacia G4 cells to survive following TCE transformation. A possible role for nucleotide excision repair and recombination repair activities in TCE-damaged cells is discussed.